FEASIBILITY AND CONCEPTUAL BASIS OF THE TRANSITION TO A GREEN ECONOMY IN THE SCIENCE OF GREEN ECONOMY (Scientific journal of the Fergana State University, 2025)
This article highlights how “green economy” can help prevent the pollution of watersheds by recycling toxic waste to improve the Uzbek economy. Ensuring the socio-Ekonomic development strategy of Uzbekistan until 2030 is a complex task to coordinate the Ekonomic, social and ecological components that are considered as means of achieving sustainable development. Ekonomic and social components set new tasks for the society, such as achieving justice and providing targeted assistance to the poor groups of the population within a generation. It led to the formation of new ideas and approaches related to the need to assess the value of the external impact of Ekonomic and ecological components on the environment. The social and ecological components of sustainable Ekonomic development increase the relevance of issues such as эnsuring эquality within and between generations.